Growth Disorders and Acromegaly (IntechOpen, 2020)
The first two years of life represent a transition period when growth changes from predominantly growth hormone (GH) independent to GH dependent. This book, Growth Disorders and Acromegaly, includes two parts. The first part consists of five chapters that illustrate the nature, causes, types, signs, and symptoms of GH deficiency (GHD) and fetal growth restriction. It describes the impact of GH and its deficiency on different biological systems in children and adults. Also, this book assesses the role of human GH (hGH) and insulin-growth factor1 (IGF-1) gene families during pregnancy. This book offers several novel insights of GH in male reproductive health. The second part consists of three chapters that show the pegvisomant, colorectal neoplasms in acromegaly, epidemiology and underlying mechanisms, and the surgical managements of acromegaly. Finally, this book will be of interest to scientists, embryologists, neuroendocrinologists, neurotoxicologists, and physicians who follow recent developments in the field of growth disorders.